2021
DOI: 10.1017/ice.2021.483
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory coronavirus virus 2 (SARS-CoV-2) nosocomial transmission dynamics, a retrospective cohort study of two healthcare-associated coronavirus disease 2019 (COVID-19) clusters in a district hospital in England during March and April 2020

Abstract: Summary Objective: To understand the transmission dynamics of SARS-CoV-2 in a hospital outbreak to inform infection control actions. Design: Retrospective cohort study. Setting: General medical and elderly inpatient wards in a hospital in England. Methods: COVID-19 patients were classified as community or healthcare-associated by time from admission to onset/positivity using European Centre for Disease Prevention and Control definitions. COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, 1 there have been reports of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission to patients and healthcare workers (HCW) within healthcare facilities. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Factors contributing to these outbreaks have included patient accommodation in multibed rooms or bays, [6][7][8]11,12,17 lack of infection prevention and control precautions due to failure to identify patients admitted with or incubating SARS-CoV-2, [6][7][8][9][10]20 and nosocomial exposure to a patient with COVID-19. [15][16][17][18][19][20] Rhee et al 22 demonstrated that consistent application of infection prevention and control measures can reduce or prevent the spread of SARS-CoV-2 in healthcare settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, 1 there have been reports of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission to patients and healthcare workers (HCW) within healthcare facilities. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Factors contributing to these outbreaks have included patient accommodation in multibed rooms or bays, [6][7][8]11,12,17 lack of infection prevention and control precautions due to failure to identify patients admitted with or incubating SARS-CoV-2, [6][7][8][9][10]20 and nosocomial exposure to a patient with COVID-19. [15][16][17][18][19][20] Rhee et al 22 demonstrated that consistent application of infection prevention and control measures can reduce or prevent the spread of SARS-CoV-2 in healthcare settings.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Factors contributing to these outbreaks have included patient accommodation in multibed rooms or bays, [6][7][8]11,12,17 lack of infection prevention and control precautions due to failure to identify patients admitted with or incubating SARS-CoV-2, [6][7][8][9][10]20 and nosocomial exposure to a patient with COVID-19. [15][16][17][18][19][20] Rhee et al 22 demonstrated that consistent application of infection prevention and control measures can reduce or prevent the spread of SARS-CoV-2 in healthcare settings. However, outbreaks in healthcare facilities continue.…”
mentioning
confidence: 99%
“…Our study is one of several observational studies exploring risk factors for patient COVID-19 acquisition in hospitals [25][26][27][28][29][30][31][32]. There were several factors which were identified during this outbreak in a setting without vaccination for any HCWs or patients which may have facilitated the transmission events to occur.…”
Section: Discussionmentioning
confidence: 98%
“…Failure to isolate symptomatic patients on symptom onset likely led to transmission via close contact [33] through either respiratory droplets/particles across a continuum of sizes, and/or contact (direct and indirect) routes of transmission within shared rooms/bathrooms. A retrospective cohort study found in a crude analysis of 122 patients across three outbreak wards that being exposed to a symptomatic COVID-19 patient within the same 4-bed bay regardless of proximity in the room was associated with doubling the risk of becoming a case (crude RR, 2.3, 95% CI 1.42-3.65) [27]. In a matched case-control by Aghdassi et al [28], the multivariate analysis revealed that presence on a ward that experienced a COVID-19 outbreak (aOR 15.9, 95% [28].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 is highly stable in aerosol and on surfaces compared to SARS-CoV-1, maintaining the virus infectious for hours in the aerosol (Anfinrud et al, 2020;Morawska and Cao, 2020;Paules et al, 2020;van Doremalen et al, 2020;Ong et al, 2021). These facts imply that in the absence of face masks the distance of 1-2 m among people is not enough to safeguard from SARS-CoV-2 infection risk (Parshina-Kottas et al, 2020), as it has been reported to happen in hospitals (i.e., SARS-CoV-2 RNA has been detected in air samples collected inside the hospitals, thereby the airborne route has to be considered an important pathway for contamination), schools and other indoors spaces (Liu et al, 2020f;Nissen et al, 2020;Santarpia et al, 2020;Akhmetzhanov et al, 2021;Chau et al, 2021;Ding et al, 2021;Kumari et al, 2021;Leeman et al, 2022;Marchese et al, 2021;Miyoshi et al, 2021;Murewanhema et al, 2021;Ong et al, 2021;Salmenjoki et al, 2021;Sami et al, 2021;San et al, 2021;Jung et al, 2022;Kirsten et al, 2022;Ladhani et al, 2022;Leng et al, 2022;Nagy et al, 2022;Polechova et al, 2022;Viner et al, 2022;White et al, 2022). Therefore, SARS-CoV-2 is transmitted by bioaerosols (<10 μm) and droplets (>10 μm) projected during breathing, speaking and coughing (Klompas et al, 2020a;Binder et al, 2020;Liu et al, 2020f;Nissen et al, 2020;van Doremalen et al, 2020;Zhang and Duchaine, 2020;...…”
Section: Physical Barriers For Prevention: Face Masks and Protective ...mentioning
confidence: 99%